2002
DOI: 10.1002/mrc.1024
|View full text |Cite
|
Sign up to set email alerts
|

1H and 13C NMR spectral characterization of some antimalarial in vitro 2,4‐diamino‐10‐methylpyrimido[4,5‐b]‐5‐quinolone derivatives

Abstract: We report the 1 H NMR and 13 C NMR chemical shifts and J(H,H), J(H,F) and J(C,F) coupling constants of 13 2,4-diamino-10-methylpyrimido[4,5-b]-5-quinolone derivatives, some of them with moderate activity against Plasmodium falciparum in vitro. They were characterized and assigned on the basis of 1 H, 13 C and 13 C-1 H (short-and long-range) correlated spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…2,3 As part of a general project we have begun to develop new, more effective, antimalarial drugs, and a number of quinoline, quinolone, pyrimidone, pyridopyrimidone, thiocromone and pyrazole derivatives have been synthesised, characterised and tested for antimalarial activity. [4][5][6][7][8] Recently, we synthesised several N-methylated tricyclic quinolones that were found to have moderate in vitro and in vivo activity against a chloroquine resistant strain of P. falciparum. 9,10 Among these derivatives, the biological results suggested that 1 displayed a moderate antimalarial activity which was associated with the formation of an intramolecular N-H•••O =C hydrogen bond (vide infra).…”
mentioning
confidence: 99%
“…2,3 As part of a general project we have begun to develop new, more effective, antimalarial drugs, and a number of quinoline, quinolone, pyrimidone, pyridopyrimidone, thiocromone and pyrazole derivatives have been synthesised, characterised and tested for antimalarial activity. [4][5][6][7][8] Recently, we synthesised several N-methylated tricyclic quinolones that were found to have moderate in vitro and in vivo activity against a chloroquine resistant strain of P. falciparum. 9,10 Among these derivatives, the biological results suggested that 1 displayed a moderate antimalarial activity which was associated with the formation of an intramolecular N-H•••O =C hydrogen bond (vide infra).…”
mentioning
confidence: 99%